Role of Multi-Detector Computed Tomography in Evaluating Traumatic Brain Injuries in Taif City, Kingdom of Saudi Arabia - Muyini, Mohammed Jaber Ahmed; Almalki , Abdulaziz Turki Abdulaziz; A.Fafi, Abdulaziz Yahya; Alqahtani, Abdulwahab Abdullah; Al-Malki, Anas Jamaan Ahmad; Morwea, Ali Nasser Hussein; Alqahtani, Ibrahim Abdulrahman; Alshanbari, Hazza Naser; Talhi, Adnan Matouq Al; Alahmadi, Ghassan Saeed (Journal of Ecohumanism, 2024)
Background: Traumatic brain injury (TBI) represents a major percentage of admissions to hospital due to frequent trauma to this region and is considered a life-threatening situation because of that, MDCT is necessary to provide rapid diagnosis and best management that leads to successful treatment. Multi-detector Computed Tomography (MDCT) has a critical and significant rule for early evaluation and patient triage. Aim: This study aimed to evaluate the findings that occur due to head injuries using MDCT. Material and Method: An analytical retrospective study of 200 patients with head injuries were examined by CT, the study extended from January 2024 to September 2024. 128 slice CT systems (Siemens Medical system) were applied to investigate patients with head trauma at King Abdul-Aziz Specialist Hospital (KAASH )in Ta’if City, Saudi Arabia. Results: A total of 200 head trauma 136 (68%) males and 64(32%) females, were examined via head CT and presented with various types of trauma. The findings have noticed that brain injuries were significantly higher in the male population (68%) than in the female population (32%). Based on age groups, the incidence percentage of TBI was 34%, occurring in the age group 18-27 years. The most common cause of injury in patients presenting with head trauma was road traffic accidents, comprising 63% of cases. The isolated skull fracture was most frequently seen 35% of cases. Our study reveals that Subdural hematoma (52%) was the most frequent lesion noted in traumatic patients. Conclusion: Non-enhanced computed tomography( NECT) is considered the gold standard and the most informative diagnostic modality in the evaluation of Traumatic brain injuries and it is essentially to triage patients to observation, surgical, or medical management.